Dynamic target high pressure control of a VRF system for heating energy savings. (25th February 2017) - Yun, Geun Young; Lee, Je Hyeon; Kim, Inhan
Highlights: We developed the dynamic target high pressure control of a VRF system. We created the VRF control model using the EnergyPlus runtime language. Multicalorimeter experimental results indicate that the energy efficiency improved by 21%. EnergyPlus simulations demonstrate that the annual heating energy consumption was lowered by 22%. Abstract: Variable refrigerant flow (VRF) systems are widely used because of their ability to provide individualized comfort control with energy-saving potential. This study develops load responsive high pressure control of a VRF system with the aim of reducing the heating energy consumption of a VRF system under part load conditions. The developed control consists of two parts: one part that determines the level of heating load, and the other that assigns a target high pressure based on the level of heating load. In this way, the compressor speed can be accurately matched to heating load, which improves the energy performance of the VRF system. A series of multicalorimeter experiments revealed that the heating capacity of the VRF system varied by 45% by modulating the target high pressure and that its efficiency was enhanced by 21% by changing the high pressure from 30 kgf/cm 2 to 25 kgf/cm 2 . To evaluate the annual heating energy performance of the VRF system with the developed control, a custom computer code was developed to implement the developed control using a programming language called EnergyPlus Runtime Language. Simulation outcomes showed that the annual heating energy consumption of a medium-size office building was reduced by 22% when the developed control was applied.